(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
This study is ensuring the standard operative process (SOP) of Sharpunkha Kshar (Lavana) (alkaline extract of Tephrosia purpuria Linn.), as per classical text. It has hepato-protective effect. Many researches have been done on Sharpunkha extract but, no one work has been done on standardization of Sharpunkha Kshar (Lavana) yet. It was 1st mentioned by Acharya Bhavprakash in Gulma chikitsa prakaran by the name of Sharpunkha Lavana. During standardization of Sharpunkha Kshar (Lavana) raw drug authentication was done by microscopic and physico chemical analysis. lupeol, rutin, quercetin, rotenone and beta sitosterol biomarkers were screened in raw Sharpunkha panchang powder in HPTLC finger printing. Kshara was prepared by two different methods with 4 times (SPK-4) 6 times (SPK-6) water following standard protocols. Average 46.44% yield was obtained after drying of fresh Sharpunkha panchang. After burning of dry Sharpunkha average 5.03% ash was achieved. Average 16.3% Kshar yield in batch SK-4 and 16.6% Kshar yield in SK-6 was obtained. One more batch from residual ash was also prepared, 6.64% Kshar was obtained in it. Organoleptic, physico-chemical parameters were also done for both batch of Sharpunkha Kshar (Lavana). pH (12.65 & 13.35 in SK-4, SK-6 respective) carbonate, bicarbonates, Na (0.56 & 0.52%), and K (35.26, 35.41%) respectively present in batch SK-4 & SK-6.